The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.4097/kja.22441
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative nausea and vomiting between remimazolam and propofol: a propensity score-matched, retrospective, observational, single-center cohort study

Abstract: This article has been accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination, and proofreading processes, which may lead to differences between this version and the version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 22 publications
1
15
1
Order By: Relevance
“…Surprisingly, PONV was similar in the operating room and ward in both groups, contrary to the expectation that propofol might reduce PONV compared with remimazolam. 16 Also, the mean HR after induction was significantly lower in the propofol than remimazolam group. This finding is consistent with the fact that propofol may induce haemodynamic instability, such as bradycardia, because of the narrow therapeutic window.…”
Section: Discussionmentioning
confidence: 86%
“…Surprisingly, PONV was similar in the operating room and ward in both groups, contrary to the expectation that propofol might reduce PONV compared with remimazolam. 16 Also, the mean HR after induction was significantly lower in the propofol than remimazolam group. This finding is consistent with the fact that propofol may induce haemodynamic instability, such as bradycardia, because of the narrow therapeutic window.…”
Section: Discussionmentioning
confidence: 86%
“…[3] It has been reported that the incidence of hypotension, bradycardia and injection pain of remimazolam is lower than that of propofol in general anesthesia, but it is inferior to propofol in preventing PONV. [4,5] Antiemetics such as dexamethasone, droperidol and tropisetron are commonly used, but each has its own side effects and increases the medical burden on the patient. [6,7] Hvarfner et al [8] found that small doses of propofol also had an anti-nausea and vomiting effect.…”
Section: Introductionmentioning
confidence: 99%
“…[3] It has been reported that the incidence of hypotension, bradycardia and injection pain of remimazolam is lower than that of propofol in general anesthesia, but it is inferior to propofol in preventing PONV. [4,5]…”
Section: Introductionmentioning
confidence: 99%
“…[2] Total intravenous anesthesia provides better quality of recovery and enables intraoperative monitoring of the somatosensory or motor-evoked potentials. [4][5][6] Propofol is the most commonly administered hypnotic agent for total intravenous anesthesia. [4] Remimazolam, a novel short-acting benzodiazepine, is an alternative hypnotic drug to propofol.…”
Section: Introductionmentioning
confidence: 99%